Karakteristik klinis dan lama rawat inap pasien covid-19 dengan kormobid dan tanpa kormobid - Erika Martining Wardani; Difran Nobel Bistara; Yurike Septianingrum (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Covid-19 infects people with different clinical, from mild to moderate clinical symptoms even recovering without hospitalization. The clinical course of COVID-19 patients with comorbidities influences the prognosis and progression of the disease. Hypertension is the most common co-morbidity of COVID-19 patients with long hospitalizations.Purpose: Of the study was to determine the differences in patient characteristics, clinical and length of stay for COVID-19 patients with and without cormobids.Method: A retrospective study with samples of medical records of inpatients for the period June 1, 2021 – August 31, 2021. The samples were divided into 2 groups, namely kormobid with 30 medical records and without cormobid with 30 medical records. The sample of the comorbid group was selected by simple random; while the non-cormobid group with the matching process. Data were analyzed using t-test and Wilcoxon.Results : The majority of COVID-19 patients with comorbidities are male, aged more than 40 years, work other than medical personnel, while most of the COVID-19 patients without cormobids are male, aged 12-29 years, working as medical personnel. Cormobid with hypertension. Clinically treated COVID-19 patients include cough, fever, headache, runny nose, painful swallowing, anosmia, shortness of breath, nausea, vomiting and diarrhea. The length of hospitalization for patients with comorbidities was 21 days and without comorbidities 14 days. There were clinical differences between patients with comorbid and non-cormobid patients with p value = 0.0000 (p>0.05) and there was a difference in length of hospitalization with p-value = 0.000 (p>0.05).Conclusion : Clinically, patients with covid-19 with comorbidities differ in headache symptoms with a longer treatment duration of 22 days. Intensive care is needed for COVID-19 patients with comorbid hypertension.Keywords: Characteristics; Clinical features; Treatment duration; Covid-19Pendahuluan : Covid-19 menginfeksi orang dengan klinis yang berbeda, dari gejala klinis ringan sampai sedang bahkan sembuh tanpa rawat inap. Klinis pasien covid-19dengan komorbiditas mempengaruhi prognosis dan perkembangan penyakit tersebut. Hipertensi merupakan penyakit penyerta terbanyak pasien covid-19 dengan rawat inap lama.Tujuan: Mengetahui perbedaan karakteristik, klinis pasien dan lama rawat inap pasien covid-19 dengan kormobid dan tanpa kormobid.Metode : Penelitian secara retrospektif dengan sampel rekam medis pasien rawat inap periode 1 Juni 2021 – 31 Agustus 2021. Sampel dibagi menjadi 2 kelompok yaitu kormobid dengan 30 rekam medis dan tanpa kormobid dengan 30 rekam medis. Sampel kelompok kormobid dipilih secara simple random; sedangkan kelompok non kormobid dengan proses matching. Data dianalisis menggunakan t-test dan Wilcoxon.Hasil : Mayoritas pasien covid-19 dengan kormobid berjenis kelamin laki-laki, usia lebih dari 40 tahun, pekerjaan selain tenaga medis sedangkan pasien covid-19 tanpa kormobid sebagian besar laki-laki, usia 12-29 tahun, pekerjaan sebagai tenaga medis. Kormobid yang diderita hipertensi. Klinis pasien covid-19 yang dirawat meliputi batuk, demam, nyeri kepala, pilek, nyeri telan, anosmia, sesak, mual, muntah dan diare. Lama rawat inap pasien dengan komorbid 21 hari dan tanpa komorbid 14 hari. Terdapat perbedaan klinis pasien antara pasien kormobid dan non kormobid dengan nilai p = 0,0000 (p>0,05) dan ada perbedaan lama rawat inap dengan nilai p=0,000 (p>0,05). Simpulan : Klinis pasien covid-19 dengan kormobid berbeda pada gejala nyeri kepala dengan lama perawatan lebih lama yaitu 22 hari. Perlu perawatan intensif pada pasien covid-19 dengan kormobid hipertensi.